Detection of pulmonary surfactant protein A by using an aptamer-based liquid crystal biosensor. Issue 24 (7th June 2018) - Wang, Ying; Wang, Bing; Zhang, Qingli; Xiong, Xingliang; Deng, Shixiong
Abstract : An aptamer-based liquid crystal biosensor for the detection of pulmonary surfactant protein A has been presented. Abstract : This paper reports a novel detection method for pulmonary surfactant protein A (SP-A) using an aptamer-based liquid crystal (LC) biosensor. The LC molecules are supported on the surface of glass slides modified with an appropriate amount of SP-A aptamers, causing a homeotropic orientation of LCs. The specific interaction between the aptamer and SP-A induces great changes of the topology on the surface. The changes will disrupt the homeotropic orientation of LCs, resulting in an optical appearance transition of the polarized image. Therefore, SP-A can be easily recognized. The results can be quantitatively determined through image analysis. The limit of detection is only 5 nM. The presented strategy provides a simple aptamer-based sensing platform for biomolecule recognition, owing to its characteristics of being label-free, low-cost and highly specific, and having no requirement of instrumental read-out.